Low-frequency maternal novel MYH7 mosaicism mutation in recurrent fetal-onset severe left ventricular noncompaction: a case report - Kawamura, Hiroshi; Ikawa, Masamichi; Hirono, Keiichi; Kimura, Junya; Okuno, Takashi; Kawatani, Masao; Inai, Kunihiro; Hata, Yukiko; Nishida, Naoki; Yoshida, Yoshio (Frontiers in Pediatrics, 2023)
Background: Left ventricular noncompaction (LVNC) is a rare inherited cardiomyopathy with a broad phenotypic spectrum. The genotype-phenotype correlations in fetal-onset LVNC have not yet been fully elucidated. In this report, we present the first case of severe fetal-onset LVNC caused by maternal low-frequency somatic mosaicism of the novel myosin heavy chain 7 (MYH7) mutation. Case presentation: A 35-year-old pregnant Japanese woman, gravida 4, para 2, with no significant medical or family history of genetic disorders, presented to our hospital. In her previous pregnancy at 33 years of age, she delivered a male neonate at 30 weeks of gestation with cardiogenic hydrops fetalis. Fetal echocardiography confirmed LVNC prenatally. The neonate died shortly after birth. In the current pregnancy, she again delivered a male neonate with cardiogenic hydrops fetalis caused by LVNC at 32 weeks of gestation. The neonate died shortly after birth. Genetic screening of cardiac disorder-related genes by next-generation sequencing (NGS) was performed which revealed a novel heterozygous missense MYH7 variant, NM_000257.3: c.2729A>T, p.Lys910Ile. After targeted and deep sequencing by NGS, the same MYH7 variant (NM_000257.3: c.2729A>T, p.Lys910Ile) was detected in 6% of the variant allele fraction in the maternal sequence but not in the paternal sequence. The MYH7 variant was not detected by conventional direct sequencing (Sanger sequencing) in either parent. Conclusions: This case demonstrates that maternal low-frequency somatic mosaicism of an MYH7 mutation can cause fetal-onset severe LVNC in the offspring. To differentiate hereditary MYH7 mutations from de novo MYH7 mutations, parental targeted and deep sequencing by NGS should be considered in addition to Sanger sequencing.